Use of Opioids Increases With Age in Older Adults: An Observational Study (2005–2017) - Weesie, Yvette M.; Hek, Karin; Schermer, Tjard R. J.; Schellevis, Francois G.; Leufkens, Hubertus G. M.; Rook, Elisabeth J.; van Dijk, Liset (Frontiers in Pharmacology, 2020)
Aim: Pain is increasingly treated with opioids. Potential harms of opioid therapy disproportionally affect older patients. This study aims to provide information on trends, nature and duration of opioid prescribing to older adults, in primary care and to explore differences between older patients from different ages. Methods: Primary care data (2005-2017) were derived from routine electronic medical records of patients in Nivel Primary Care Database. All opioid prescriptions with ATC–code N02A were selected (except for codeine). Diagnoses were recorded using ICPC-classification. Patients were categorized in three age groups (65-74, 75-84 and ≥85 years). Descriptive analyses were used to describe the trend of opioid prescriptions for specific opioids, the duration of use and underlying diagnoses. Results: 283,600 patients were included of which 32,287 had at least one opioid prescription in 2017. An increase in the number of older adults who received at least one opioid was seen between 2005 and 2017. The oldest patients were more likely to be prescribed an opioid, especially when it comes to strong opioids duration, the increase in the volume of prescribing was highest in this group. Moreover, over 40% of the patients used strong opioids chronically, these were mostly prescribed for musculoskeletal diagnoses. Cancer was the second most common diagnosis for strong opioids in the younger subgroups, whereas less specified diagnoses were as second in the oldest subgroup. Conclusion: Opioid prescription changes with increasing age in frequency, nature and duration, despite higher harm risks among older patients. Because of the high prevalence of chronic use, it is important to monitor the patient throughout the treatment and to critically evaluate the initiation and continuation of opioid prescriptions.